Flipsnack-assisted IPAS E-Modules: Substance Forms and Changes for Student Engagement - Novi Wulandari; Zulherman (Jurnal Penelitian Pendidikan IPA, 2024)
Fun learning in the classroom is the use of interactive and innovative media because the use of media can make student active. But in reality, there are many factors that cause students to be inactive in the classroom, one of which is the use of media that in still not interesting. This creation of thi flipsnack-assisted E-module development aims to increase student activeness.  The method used is Research and Development (R&D) the model used is the ADDIE model. This research was conducted in two schools, namely SDN Kapuk 02 Pagi & SDN Cijantung 03 Pagi. With research subjects of 120 grade IV students using control class and experimental class. Direct observation and testing were the methods used for data collection. In this study, researchers conducted validation, the validation carried out was validation of language, material, and media. Media expert validation results were 92% categorized as "very worthy", 94% material experts categorized as "very worthy", and 87% language experts categorized as "very worthy". Additionally, validation was done by students by filling out questionnaires with 93%  results categorized as "very worthy". And in the Score N-Gain test, the average N-Gain value of the experiment class was 62,50% categorized as "quite effective", and in the control class only 24%. Based on the outcomes, it shows that the use of E-modules can increase student activeness in IPAS lessons on the material of the form of substances and their changes.